The art and science of leadership - Nahavandi, Afsaneh (Upper Saddle River, N.J. : Pearson Prentice Hall, 2009)
Along with strong theoretical coverage and introduction of cutting-edge research, this book continues to be application focused and encourages students to apply the theory to their own development and into their current organizations One of the goals for this text is to include cross-cultural, racial, and gender-based analyses of leadership as a major part of the discourse about leadership effectiveness. The changing demographics within the United States and the globalization of the world economy make such analysis essential.
Definition and significance of leadership -- The global and cultural contexts -- Early theories -- Individual differences and traits -- Power and leadership -- New models for leadership -- Other leadership perspectives -- Participative management and leading teams -- Leading change -- Developing leaders.
Includes bibliographical references (p. 359-392) and indexes.
1
Keywords: MOT; Leadership; Leadership -- Cross-cultural studies